HUBUNGAN KETAHANAN PANGAN KELUARGA DAN TINGKAT KONSUMSI ZAT BESI DENGAN KEJADIAN ANEMIA DAN PRESTASI BELAJAR PADA REMAJA PUTRI - Novita, Tri Liana; Ningtyias, Farida Wahyu; Ratnawati, Leersia Yusi (Journal of Nutrition College, 2024)
ABSTRACTBackground: Low learning achievement is one of the impacts of anemia. Factors causing anemia in adolescent girls include family food security and iron consumption levels. Anemia in adolescent girls requires special attention, considering that the impact is very detrimental so can be prevented and overcome to increase productivity and cognitive abilities.Objectives: This study aims to analyze the relationship between family food security and iron consumption level with the incidence of anemia and learning achievement in adolescent girls.Methods: The study used observational analytics with a cross sectional approach. The sample was high school adolescent girls in Pakusari District as many as 86 subjects aged of 16-18 years using proportional random sampling and carried out in March-May 2023. The independent variables in this study are family food security and iron consumption levels, and the dependent variables are anemia and learning achievement in adolescent girls. Data collection was conducted by interview using 2x24 hour food recall questionnaire and Self-Administered Food Security Survey Module for Children Ages 12 Years and Older, measurement of hemoglobin levels and documentation of student report cards. Bivariate analysis was conducted using chi-square and coefficient contingency.Results: Statistical results showed a relationship between family food security (p=0.001; C=0.343) and iron consumption level (p=0.000; C=0.595) with the incidence of anemia. Food security showed a weak relationship while the level of iron consumption was moderately strong. There was also a weak relationship between family food security (p=0.004; C=0.338) and iron consumption level (p=0.005; C=0.333) with learning achievement.Conclusion: There is a relationship between family food security and iron consumption level with the incidence of anemia and learning achievement among high school girls in Pakusari District, Jember Regency.Keywords : Food security; iron; anemia; learning achievement, adolescent girls                                                    ABSTRAKLatar belakang: Capaian prestasi belajar yang rendah merupakan salah satu dampak dari anemia. Faktor penyebab anemia pada remaja putri diantaranya adalah ketahanan pangan keluarga dan tingkat konsumsi zat besi. Anemia remaja putri memerlukan perhatian khusus mengingat dampak yang ditimbulkan merugikan sehingga dapat dicegah dan ditanggulangi untuk meningkatkan produktivitas dan kemampuan kognitif.Tujuan: Penelitian ini bertujuan untuk menganalisis hubungan antara ketahanan pangan keluarga dan tingkat konsumsi zat besi dengan kejadian anemia dan prestasi belajar pada remaja putri.Metode: Penelitian menggunakan analitik observasional dengan pendekatan cross sectional. Sampel adalah remaja putri SMA/sederajat di Kecamatan Pakusari sebanyak 86 subjek dengan rentang usia 16-18 tahun menggunakan proportional random sampling dan dilaksanakan pada bulan Maret-Mei 2023. Veriabel bebas pada penelitian ini adalah ketahanan pangan keluarga dan tingkat konsumsi zat besi, variabel terikat adalah anemia dan prestasi belajar pada remaja putri. Pengumpulan data dilakukan dengan wawancara menggunakan kuesioner food recall 2x24 jam dan Self-Administered Food Security Survey Module for Children Ages 12 Years and Older, pengukuran kadar hemoglobin dengan Easy Touch (GCHb) dan dokumentasi rapor siswa. Analisis bivariat menggunakan chi-square dan coefficient contingency.Hasil: Hasil statistik menunjukkan bahwa terdapat hubungan antara ketahanan pangan keluarga (p=0,001; C=0,343) dan tingkat konsumsi zat besi (p=0,000; C=0,595) dengan kejadian anemia. Dimana ketahanan pangan menunjukkan hubungan yang lemah sedangkan tingkat konsumsi zat besi berhubungan cukup kuat. Hubungan yang lemah juga pada ketahanan pangan keluarga (p=0,004; C=0,338) dan tingkat konsumsi zat besi (p=0,005; C=0,333) dengan prestasi belajar.Simpulan: Terdapat hubungan antara ketahanan pangan keluarga dan tingkat konsumsi zat besi dengan kejadian anemia dan prestasi belajar pada remaja putri SMA/sederajat di Kecamatan Pakusari, Kabupaten Jember.Kata Kunci : Ketahanan pangan; zat besi; anemia; prestasi belajar, remaja putri